Czy warto jeszcze badać polsko-łacińskie kontakty językowe? Historyczny przegląd i ocena badań polsko-łacińskich kontaktów językowych - Lenartowicz-Zagrodna, Anna (Acta Universitatis Lodziensis. Folia Linguistica, 2014)
The subject of observation was the state of research on Polish-Latin language contacts. The analysis was conducted from the chronological and thematic perspective. Primary objective was to identify thematic areas that require further investigation.